PEMANFAATAN SAMPAH ORGANIK MELALUI SOSIALISASI DAN PELATIHAN LUBANG RESAPAN BIOPORI DAN ECO-ENZYME DI DUSUN 1 DESA LIMBANGAN TENGAH - Sri Rahayu; Arrly Azizah Fadjar; Fajwah Nurchalijah; Reyhan Maliq; Azhar Mochamad Akhmad; Miftahul Fikri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The issue of organic waste management in rural communities, particularly in Hamlet 1 of Limbangan Tengah Village, remains a challenge due to a lack of knowledge and skills in processing household waste in an environmentally friendly manner. This has led to an increase in waste volume and the potential for environmental pollution in the surrounding area. This community service activity aims to enhance the community’s capacity to utilize organic waste through outreach and training on the construction of biopore infiltration pits and the use of eco-enzymes as alternative solutions for organic waste management. The implementation methods include participatory outreach, technical demonstrations, and hands-on practice with residents. The results of the activity demonstrate an increase in residents’ knowledge and skills in independently creating and applying biopore and eco-enzyme technologies. The impact is evident in the implementation of these two technologies within residents’ homes, contributing to a reduction in the volume of organic waste and an increase in environmental awareness. The uniqueness of this program lies in the integration of two simple yet effective organic processing methods, combined with a hands-on, practice-based educational approach. As a recommendation, similar activities should be continued with ongoing support and expanded to other villages to promote a sustainable, community-based organic waste management movement.